AN ANALYSIS OF DEIXIS IN LITTLE WOMEN MOVIE SCRIPT - Rusmana, Syarah Syahidah; Syahrizal, Trisnendri; Kusnadi, Kusnadi (IKIP Siliwangi, 2024)
This study aimed to analyzing types and studying the use of deixis frequency in the Little Women movie script, namely personal deixis, place deixis, time deixis, and deixis discourse, which only fits in dialogues in film scripts. This study also aims to determine the type of dominant deixis used in the film Little Women. This study used a descriptive qualitative method. This research was carried out in the following stages; 1) watch and collect all related data in the film. 2) categorize existing data according to the type of deixis. 3) analyze data related to the kind of deixis. 4) displays related data. 5) explain the data in every type of deixis. In this study, the most dominant deixis used was personal deixis, with a total frequency of 1958 (78%). Next, deixis is the deixis discourse with 365 (14,38%) frequencies appearing. Third, time deixis with frequency appears 131 (5,16%). The last is place deixis with frequencies 85 (3,35%).